Role of multi-strain probiotics in preventing severity and frequency of recurrent respiratory tract infections in children - Imran Khan Laghari; Tahira Nawaz; Sultan Mustafa; Abid Ali Jamali; Sanober Fatima (BMC, 2023)
Abstract Background Respiratory tract infections are among the most common infections in the pediatric population throughout the globe. Globally around 20% of all deaths in children below 5 years of age are secondary to acute respiratory infections, mostly pneumonia. Probiotics are live microorganisms that when administered in adequate amounts confer a health benefit on the host. Their mechanism in preventing respiratory tract infections is not known but it is thought that probiotics act by modulating the immune system. This study was conducted to find out whether using probiotics is effective in decreasing the severity and frequency of recurrent respiratory tract infections or not. Methods A Quasi-experimental study was conducted at the Pediatric Medicine Department of Abbassi Shaheed Hospital Karachi during 2021-2022. The study was approved by the institutional ethical review committee i.e. advanced studies and research board (ASRB). The sampling technique was non-probability consecutive sampling and the sample size was 70 patients with recurrent respiratory tract infections, aged six months to 12 years of age. All enrolled children were given probiotics containing Bifidobacterium, Lactobacillus Acidophilus for two weeks. Data were analyzed by using SPSS version 22. A p-value of < 0.05 was considered statistically significant. Results Out of 70 children with recurrent respiratory tract infections, 39 (55.71%) were male and 31 (44.29%) female. Around 75% of the children were below five years of age. The most common presenting complaint was fever (72.86%), followed by cough (68.57%), wheezes (45.71%) and nasal discharge/sneezing (32.86%), respectively. The most common RRTI was infectious rhinitis (30% of the cases), otitis media (24%) and pharyngitis/tonsillitis (21%). After giving probiotics for two weeks most significant decrease was found in recurrent infectious rhinitis (p-value 0.02), recurrent otitis media (p-value 0.03) and recurrent bronchiolitis (p-value 0.05) over the next six months. Conclusion The results of our study indicate that the administration of probiotics reduces recurrent respiratory tract infections among children. This six months trial has demonstrated that there was a significant decline in respiratory symptoms among study participants. This study also observed a significant decrease in respiratory diseases during the follow-up.